A Review of Parabolic Dish-Stirling Engine System Based on Concentrating Solar Power - Liaw Geok Pheng; Rosnani Affandi; Mohd Ruddin Ab Ghani; Chin Kim Gan; Zanariah Jano; Tole Sutikno (Universitas Ahmad Dahlan, 2014)
A solar thermal technology which is also known as concentrating solar power (CSP) uses thermal energy from the sun to generate electricity. The electricity generation from solar thermal can be produced with four technologies of concentrating solar systems which are parabolic trough, linear Fresnel reflector, solar tower, and parabolic dish-Stirling engine system. This paper reviews the parabolic dish-stirling based on CSP technology by taking into account the performance, the global performance, site for parabolic dish and levelized cost of energy (LCOE). Generally, the parabolic dish applications have barriers in terms of the technology and the high capital cost compared to the others CSP technologies.